(untitled) (Biological Sciences - PJSIR, 1999)
Growth and production of extracellular polysaccharides (EPs) by the unicellular red alga Porphyridiuin cruentum were studied in open vessels of different depths under outdoor natural climatic conditions of Pakistan and compared with cultures grown under indoor controlled conditions. In 2 ern deep cultures both growth and EPs production were found to be higher in indoor cultures than the outdoor cultures whereas in 8 cm deep cultures, both growth and EPs production were found to be higher in outdoor cultures. In this case, an increase of58% in biomass and 163% in EPs production was observed in the outdoor cultures as compared to indoor cultures. During outdoor cultures, the depth of8 ern was noted to be most optimum for both biomass and EPs production. Also, polysaccharides produced under outdoor conditions compared well with a number of currently used biopolymers regarding rheological properties.